Lex Parsifal – the Melange of Law, Art and Politics - Skrzywanek-Jaworska, Dagmara; Tomasz Tadajczyk, Konrad (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The article concerns a melange of artistic and political dependencies that were to help the Wagnerians to change the law in force. The story takes place at the turn of the 19th and 20th centuries in the German Reich. The law is personified by the change in the duration of copyright, art – by Richard Wagner’s Parsifal, and politics – by a group of intellectuals with strong nationalist views.